PENGARUH DAYA DUKUNG TANAH DALAM PENENTUAN PONDASI BORED PILE DAN PILE CAP PADA GEDUNG BERTINGKAT - Nurokhman, Nurokhman; Iskandar, Muhammad Ryan; Hanafi, Nufrizal Farid; Marasabessy, Muhammad Irfan (Fakultas Teknik Universitas Cokroaminoto Yogyakarta, 2023)
In building design, the problem of soil investigation is to determine the property value and property engineering which determines the selection of the foundation type and its depth. Generally, soil investigations are carried out by means of sondir and drilling which are then calculated with a certain formula to determine the bearing capacity of the soil. The purpose of this study is to identify soil properties at the project site, evaluate the results of soil investigations, and bored pile foundation design. The research method is to collect data from reference sources that are directly related to designing, especially PT. Poladata Consultant Consultants, and direct surveys to the location through systematic stages. Results soil investigation, the Cone Penetration Test (CPT) soil test at the site location of the UGM Faculty of Law Building was carried out at 2 points (S-1 and S-2) which shows the groundwater level at an elevation of -4.00 m, and soil drilling or Standard Penetration Test (SPT) at a depth of -13.40 m, the value of qc conus resistance reaches> 600 kg / cm2. The carrying capacity of the bored pile from the SPT data uses the Reese & Wright method for the case study F1 foundation is installed with 4 bored piles diameter (d) = 0.8 m2, depth (L) = 23-28 m, carrying capacity (qp) = 272.328 T/m2, Safety Factor (SF) = 3, with a piece size of 3.6 m x 3.6 m thick 1.2 m with reinforcement D16-120 mm.